2019
DOI: 10.1002/clc.23300
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial left ventricular lead implantation in cardiac resynchronization therapy patients via a video‐assisted thoracoscopic technique: Long‐term outcome

Abstract: Background Epicardial placement of the left ventricular (LV) lead via a video‐assisted thoracoscopic (VAT) approach is an alternative to the standard transvenous technique. Hypothesis Long‐term safety and efficacy of VAT and transvenous LV lead implantation are comparable. To test it, we reviewed our experience and we compared the outcomes of patients who underwent implantation with the two techniques. Methods The VAT procedure is performed under general anesthesia, with oro‐tracheal intubation and right‐sided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…In contrast, our data revealed that the VATS epicardial LV lead implantation without sternotomy showed satisfactory and comparable long-term (34.3 ± 28.6 months) outcomes with regards to LV lead performance, electro-/echocardiographic improvement, and clinical prognosis of patients compared with those using a conventional endocardial approach. Our results are in line with data from Marini et al, who demonstrated no differences in death, cardiovascular hospitalizations, or devicerelated complications between the Epicardial (thoracoscopically implanted) and Endocardial groups during a median followup of 24 months 19 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, our data revealed that the VATS epicardial LV lead implantation without sternotomy showed satisfactory and comparable long-term (34.3 ± 28.6 months) outcomes with regards to LV lead performance, electro-/echocardiographic improvement, and clinical prognosis of patients compared with those using a conventional endocardial approach. Our results are in line with data from Marini et al, who demonstrated no differences in death, cardiovascular hospitalizations, or devicerelated complications between the Epicardial (thoracoscopically implanted) and Endocardial groups during a median followup of 24 months 19 .…”
Section: Discussionsupporting
confidence: 93%
“…However, most of the previous data were derived from patients treated by sternotomy or thoracotomy, which is more invasive treatment than thoracoscopic surgery 9,10,17 . Although a small number of studies were carried out on thoracoscopic epicardial LV lead implantation, the e cacy of CRT using the VATS approach was not compared using endocardial LV leads; if ever compared, only for a short period (6-12 months) 18, 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, during CRT, epicardial lead implantation via minimally invasive left-sided thoracotomy is safe, feasible, and effective. Our findings corroborate those of Marini et al, who reported a similar length of hospital stay, complication rate, and improvement in ventricular reverse remodeling and functional status between patients undergoing epicardial placement of the left ventricular lead using a video-assisted thoracoscopic technique and those undergoing the standard transvenous technique [Marini 2020].…”
Section: Discussionsupporting
confidence: 91%
“…Recently emerging minimally invasive surgical implantation techniques, like minithoracotomy, video thoracoscopy, and robotic surgery, reduce the risk of sterno-and thoracotomy, and allow all pacing modes, including resynchronization therapy [40][41][42][43]. Efficacy and mortality were usually comparable to patients with endocardial implanted systems, especially if steroid-eluting epicardial leads were used [44,45].…”
Section: Cieds In a Patient On Hemodialysismentioning
confidence: 99%